Lexical-Semantic Abilities in Children with Developmental Dysgraphia - Ћаласан, Слађана В.; Вуковић, Миле Г.; Арсић, Радомир Б. (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Empirical data indicate that children with developmental dysgraphia may exhibit various disorders in the field of linguistic structure. However, it has not yet been determined whether linguistic impairment contributes to difficulties in mastering writing skills or whether they are a joint expression. The aim of this paper is to contribute to the understanding of the relation between the development of lexical-semantic structure and the ability to write by identifying lexical-semantic abilities in children with dysgraphia. The sample included 84 students, 42 students with developmental dysgraphia, and 42 students without disabilities. The lexical-semantic abilities were assessed by means of the Semantic Test and the Test for Speech Development. The survey was conducted in three primary schools in 2016-17 in Eastern Herzegovina. The results of the study showed that children with dysgraphia achieved significantly worse results on the Semantic Test compared to children without disabilities. Lower achievement in children with developmental dysgraphia was observed in all lexical categories examined, as well as in the overall score of the Semantic Test. The results of the Speech Development Test show that children with dysgraphia have significantly lower definitions of given terms compared to their peers of typical development. It was concluded that children with dysgraphia have significantly less developed lexical-semantic abilities than children of typical development. These findings highlight the need for additional support for vocabulary development and vocabulary enhancement in children with disabilities.